Factors affecting utilisation of biosimilar medicines in England - Alnahar, Saja (2018)
Biological medicinal products (BMPs) are medicinal products extracted from, or synthesised by, a biological system. While BMPs have been proven to be effective in treating chronic and life-threatening diseases, the utilisation of these medicines was associated with creating financial burdens for healthcare systems worldwide. Expiry of patents and marketing exclusivity rights offers an opportunity to develop similar and not identical follow-on copies called ‘biosimilar medicinal products’ (BSPs). The inability to produce an identical copy of the original product is related to the heterogenic molecular nature of BMPs and the complexity of the manufacturing processes involved. The United Kingdom (UK) was frequently reported to have only a limited uptake of BSPs. Factors related to prescribers’ reservations and lack of encouraging national policies were reported to limit BSPs’ utilisation in the UK. In February 2015, the first high-cost monoclonal antibody (mAb), ‘infliximab’ (IFX-BSP), was launched; it was the first BSP to be commissioned locally compared to the previously nationally commissioned BSPs. Since its launch, there have been several encouraging national initiatives led by NHS-England and NICE. These conditions created new market daynamics that might affect uptake rates of BSPs, particularly IFX-BSP. This thesis explores factors affecting BSPs’ utilisation and integration in clinical practice in England. The aim and objectives were actualised following an explanatory sequential mixed methods design. The study’s first component assessed BSPs’ integration levels in local medicines formularies and investigated the prescribing practices of IFX-BSPs by English Acute Trusts. Guided by first component results, the second explanatory component investigated factors that led to the observed utilisation rates of IFX-BSPs. The explanatory study was achieved through 59 in-depth semi-structured interviews with healthcare professionals, who were involved in assessing, commissioning, introducing, managing and prescribing IFX-BSPs. In general, formularies screening showed that the integration levels of targeted BSPs were less than expected from a generic medicines driven market. Data showed variations in the uptake levels between therapeutic and geographical areas within Great Britain; a phenomenon which needs to be further investigated and explained. In England, assessing prescribing practice showed that with time Acute Trusts were becoming more accepting of utilising IFX-BSPs and were beginning to switch their R-BMP stabilised patients over to the BSPs. Interviews suggested that prescribers’ knowledge, experience, common medical practice, professional societies and ethical obligations had influenced prescribers’ acceptance and attitudes toward BSPs, in general, and to the switching of stabilised patients in particular. Data showed BSPs’ utilisation was not only affected by prescribers’ attitudes, but it was also influenced by pull-push dynamics between providing Acute Trusts and commissioning CCGs. The knowledge gained from this research could be used to inform the future implementation of upcoming BSPs. Insights acquired from this research regarding interactions between providers and commissioners might be extrapolated to implementing interventions locally, especially when there is an absence of nationally specific policies or guidelines.